A VECM APPROACH TO ASSESSING THE IMPACT OF ECONOMIC GROWTH, LIVESTOCK PRODUCTION INDEX, AND CROP PRODUCTION INDEX ON METHANE GAS EMISSIONS IN INDONESIA - Perangin-Angin, Elgresia Egita Br; Habibi, Hasan Bahtiar; Hasna, Nisa Fatharani; Kartiasih, Fitri (Agros Journal of Agriculture Science, 2024)
Human activity has contributed to climate change in Indonesia due to its rapid economic expansion and active participation in achieving the Sustainable Development Goals (SDGs), particularly Goal 13 on climate change mitigation. This study assesses the impact of agricultural production index, animal production index, and economic growth on methane gas emissions in Indonesia using data spanning 1990 to 2020. The Environmental Kuznet Curve idea is not supported by the results of study conducted using the Vector Error Correction Model, which indicate that economic expansion and animal production have a significant long-term effect on methane (CH4) emissions. The Granger causality test reveals a considerable impact of agriculture and livestock on GDP, as well as a two-way relationship between GDP and CH4 emissions. The analysis of the Impulse Response Function reveals the various ways in which methane emissions react to independent factors like GDP, the Livestock Production Index (LPI), and the Consumer Price Index (CPI). The cattle industry has a considerable long-term impact on methane emissions, as evidenced by the fact that after a while, variations in CH4 emissions were more influenced by LPI. These results highlight the necessity for climate-friendly, sustainable policies, such as the incorporation of anticipation measures for climate change into national planning, the advancement of technology and innovation, and the control of waste from cattle and agriculture. Keywords: GDP, LPI, CPI, Methane Emissions, VECM, SDGs, Time Series, EKC